P108 Delivering NICE Joint Pain Advice in the workplace. (23rd April 2022) - Hurley, Michael; Carter, Andrea; Irwin, Sally; Erwin, Jo
Abstract: Background/Aims: Knee, hip and back pain is ubiquitous. NICE's recommendations are that people with persistent knee, hip and/or back pain receive self-management advice about the importance of physical activity and maintaining healthy body weight. However, people worry about moving and activity which they associate with the onset of pain, fear activity may do more harm than good and consequently refrain from activity (fear-avoidance behaviour), which causes muscles, cartilage and bone atrophy and joint stiffness. Delivering NICE advice to many millions of people is problematic because of limited time and expertise needed to deliver effective lifestyle advice. We introduced a Joint Pain Advice (JPA) service to deliver NICE advice in a variety of health and community settings delivered by a variety of professionals (physiotherapists, health trainers and navigators, community pharmacists). We have now extended JPA by training occupational health and workplace champions to deliver the service in workplace settings. Methods: In workplaces, 2-3 people were trained to deliver the JPA service. This involved an initial (30-minute) assessment when the Advisor assessed participant's pain, function, activity level, body mass, taught simple self-management strategies (weight control, exercise), used behavioural change techniques (motivational interviewing, goal-setting, action/coping planning) and constructed personalised care plans. Participants were reviewed 3 times up to 6-months later, when outcome measures were repeated, progress highlighted, health messages reinforced, on-going support offered and reassurance and encouragement given. Qualitative interviews assessed people's opinions of the effectiveness and value. Results: 12 employers delivered JPA, 417 people accessed the service. Overall musculoskeletal health and function measured by the MSK-HQ increased by 8 points (CI 6.6 to 9.2), pain decreased 1 point (CI -1.33 to -0.88), number of sit-to-stand performed in 30secs increased by 2.8 (CI 2.0 to 3.6), number of days active for >30mins each week increased by 1.5 (1.1 to 1.8) and self-reported physical function increased 1.5 point (CI 1.1 to 1.8). Employer's satisfaction with JPA was good (most were considering embedding the service into their organisation) and participant attendance was good (75%), suggesting employers and employees found JPA acceptable and valuable. Problems (inappropriate referrals, failure to attend) were identified and surmounted as possible. People valued advice tailored to their individual needs, appreciated access to care, and the tangible benefits. We are currently evaluating the impact of JPA on absenteeism, presenteeism and healthcare utilisation. Conclusion: Delivering core NICE advice through a Joint Pain Advice service in workplace settings is needed, practicable, beneficial and valued. JPA has the potential to treat people in their workplaces and communities and "prevent turning people into patients". We are planning to increase the access of employees to JPA in small medium or large employers. Disclosure: M. Hurley: None. A. Carter: None. S. Irwin: None. J. Erwin: None.